Treatment of acute obstructive cholangitis - URAYAMA, Naoki; MIKURIYA, Kuniko; HARANO, Megumi; MORI, Sayaka; IWANO, Hirotoshi; RYOZAWA, Shomei; ISHIGAKI, Noriko (Tando, 2006)
Biliary drainage is the most important treatment of acute obstructive cholangitis. In the biliary drainage, there are percutaneous transhepatic biliary drainage and endoscopic biliary drainage. It is important to understand each advantages and drawbacks. The advantages of the endoscopic treatment are the following two points: (1) the diagnosis and treatment of cholangitis are possible in the same one procedure. (2) the life limitation after the treatment is little. If the endoscopic biliary drainage succeeded, it is noninvasive and effective. However, the success rate depends on the skill of the endoscopist and it has the potential to induce severe complications. This article describes the tips of endoscopic drainage.